Two modes of gypsum replacement by carbonate and native sulfur in the Lorca Basin, SE Spain - Rouwendaal, Simon E.; Birgel, Daniel; Grossi, Vincent; Aloisi, Giovanni; Guibourdenche, Laetitia; Labrado, Amanda L.; Brunner, Benjamin; Rouchy, Jean-Marie; Peckmann, Jörn (Frontiers in Earth Science, 2023)
Organoclastic sulfate reduction and bacterial sulfide oxidation have been suggested to explain the formation of authigenic carbonate and native sulfur replacing gypsum in the Lorca Basin, Spain. To gain more insight into the nature of this replacement, two types of sulfur-bearing carbonate (laminated and brecciated) from the late Miocene Lorca Basin were studied. Petrographic observations revealed that a sulfur-bearing laminated carbonate consists of clay-rich and dolomite-rich laminae with carbonate and native sulfur pseudomorphs after gypsum. Positive δ18Ocarbonate values in the laminae (δ18O = 2.6‰) and lipid biomarkers of halophilic archaea (e.g., extended archaeol) suggest formation under hypersaline conditions. Bacterial sulfate reduction, evidenced by biomarkers such as iso-C15, iso-C16, and iso-C17 fatty acids, produced hydrogen sulfide inducing the abiotic formation of organic sulfur compounds. Gypsum in the laminated carbonate likely dissolved due to undersaturation as evidenced by a low content of carbonate-associated sulfate (3668 ppm) and 34S-enriched native sulfur (δ34S = 22.4‰), reflecting sulfate limitation. Such 34S-enrichment implies limited fluid flow, which probably restricted the supply of molecular oxygen required for native sulfur formation through oxidation of hydrogen sulfide. Alternatively, sulfate-reducing bacteria may have mediated native sulfur formation directly as a stress response to environmental conditions. The formation of sulfur-bearing calcite in brecciated carbonates is due to post-depositional alteration. Negative δ18O values of the calcite (δ18O = 1.5‰) and a tenfold decrease in carbonate-associated sulfate content (752 ppm) suggest gypsum dissolution and subsequent calcite precipitation from meteoric water. Relatively 34S-depleted native sulfur (δ34S = 13.1‰) leaves it ambiguous whether meteoric water influx could have supplied sufficient molecular oxygen for oxidation of hydrogen sulfide. In case of the brecciated carbonate, methanogenesis, anaerobic oxidation of methane, and bacterial sulfate reduction apparently mediated the formation of secondary minerals as indicated by 13C-depleted lipid biomarkers representative for the respective metabolisms. This study reveals that the conditions and timing of gypsum replacement are variable – taking place (1) during or shortly after gypsum deposition or (2) significantly after sedimentation – and suggests that methanogens in addition to anaerobic methanotrophic archaea and sulfate-reducing bacteria may be involved in the mineral-forming processes in the sedimentary subsurface.